From Storage to Survival: Understanding Non-Structural Carbohydrates in Cereal Crops - Pooja Swami; Munjal, Renu; Kamboj, Aarti (Journal of Cereal Research, 2024)
Carbon, acquired by plants through photosynthesis, primarily fuels their metabolic processes and builds structural biomass. Yet, a fraction becomes non-structural carbon compounds (NCCs), including neutral lipids and non-structural carbohydrates (NSCs). NSCs, like starch and soluble sugars, are found across various cellular compartments, each with specific functions. Starch acts as a long-term carbon storage, while soluble sugars, such as sucrose, fructose, and glucose, serve diverse roles in plant growth, defense, and transport. In challenging conditions, NSCs become vital, acting as a plant’s "food pantry." Reduced growth sink activity during stress leads to NSC accumulation, crucial for survival. Osmolytes, derived from external carbohydrates, safeguard plants against desiccation and freezing by stabilizing proteins and cell membranes. NSCs are essential for overall plant well-being, as established by earlier research. Investigating their distribution, especially in crops like cereals, provides insights into growth optimization. Understanding sugar transporters and NSC regulation offers the potential to enhance crop productivity and resilience, with profound implications for future agriculture. In essence, non-structural carbohydrates are like the secret ingredients that ensure a plant’s equilibrium amidst environmental fluctuations. Unlocking their mysteries promises improved farming practices, resilient crops, and a sustainable future.